Coexistence of diabetic ketoacidosis and thyrotoxicosis: a jeopardy of two endocrine emergencies. Issue 6 (15th June 2021) - Ahmad, Soban; Yousaf, Amman; Muhammad, Shoaib; Ghaffar, Fariha
Abstract : Simultaneous occurrences of diabetic ketoacidosis (DKA) and thyroid storm have long been known, but only a few cases have been reported to date. Both these endocrine emergencies demand timely diagnosis and management to prevent adverse outcomes. Due to the similarities in their clinical presentation, DKA can mask the diagnosis of thyroid storm and vice versa. This case report describes a patient with Graves' disease who presented to the emergency department with nausea, vomiting and abdominal pain. He was found to have severe DKA without an explicit history of diabetes mellitus. Further evaluation revealed that the patient also had a concomitant thyroid storm that was the likely cause of his DKA. Early recognition and appropriate management of both conditions resulted in a favourable outcome. This paper emphasises that a simultaneous thyroid storm diagnosis should be considered in patients with DKA, especially those with a known history of thyroid disorders.